Field Dependent Student Errors in Solving Linear Algebra Problems Based on Newman's Procedure - Astutik, Erna Puji; Purwasih, Silviana Maya (Department of Mathematics Education Program IPI Garut, 2023)
Masih banyak ditemui mahasiswa yang melakukan kesalahan dalam menyelesaiakan masalah Aljabar Linier khususnya pada materi Sistem Persamaan Linier. Penelitian ini bertujuan untuk mendeskripsikan jenis dan faktor penyebab kesalahan mahasiswa field dependent (FD) dalam menyelesaikan masalah Aljabar linier berdasarkan tahapan Newman. Penelitian ini dilakukan dengan pendekatan kualitatif dengan subjek penelitian 28 mahasiswa Program Studi Pendidikan Matematika Universitas PGRI Adi Buana Surabaya Angkatan 2020. Teknik pengumpulan data dengan mengunakan tes dan wawancara. Pada tahap pertama dilakukan tes GEFT untuk mengetahui gaya kognitif setiap mahasiswa, selanjutnya mahasiswa dengan gaya kognitif FD diberikan tes penyelesaian masalah Aljabar Linier, kemudian dipilih 3 mahasiswa FD dengan kemampuan menyelesaikan masalah terendah untuk dilakukan wawancara. Teknik analisis data menggunakan Miles and Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil penelitian dapat disimpulkan bahwa kesalahan mahasiswa dalam menyelesaikan masalah aljabar linier terletak pada tahap transformasi, keterampilan proses, dan penulisan jawaban dimana mahasiswa masih mengalami kesalahan dalam penentuan operasi baris elementer dan proses perhitungan. Sedangkan faktor penyebab kesalahan mahasiswa tersebut dikarenakan adanya kesalahan pemahaman konsep, kesalahan dalam menghitung, dan kurang teliti dalam mengerjakan. Many students still make mistakes in solving Linear Algebra problems, especially in Linear Equation Systems material. This study aims to describe the types and factors that cause student error field dependent(FD) in solving linear algebra problems based on Newman's stages. This research was conducted using a qualitative approach with research subjects 28 students of the Mathematics Education Study Program at PGRI Adi Buana University Surabaya Class of 2020. Data collection techniques used tests and interviews. In the first stage, the GEFT test was carried out to determine the cognitive style of each student. Then students with the FD cognitive style were given a Linear Algebra problem-solving test, and then 3 FD students with the lowest problem-solving abilities were selected for interviews. The data analysis technique uses Miles and Huberman, including data reduction, presentation, and conclusion. Based on the study results, it can be concluded that student errors in solving linear algebra problems lie in the stages of transformation, processing skills, and writing answers, where students still experience errors in determining elementary row operations and calculation processes. While the factors that cause student errors are errors in understanding concepts, errors in calculating, and inaccuracy in working. And writing answers where students still experience errors in determining elementary row operations and the calculation process.